2007
DOI: 10.1093/ajcn/86.2.451
|View full text |Cite
|
Sign up to set email alerts
|

Aging does not impair the anabolic response to a protein-rich meal

Abstract: Background: Sarcopenia is a debilitating condition afflicting the elderly that may be facilitated by insufficient or ineffectual intake of dietary protein. We previously showed that free-form essential amino acids acutely stimulate muscle protein synthesis in both the young and the elderly. However, the ability of an actual protein-rich food to stimulate anabolism in the young and the elderly has not been explored. Objective: We aimed to characterize changes in plasma amino acid concentrations and to quantify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
151
4
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(181 citation statements)
references
References 29 publications
14
151
4
9
Order By: Relevance
“…However, data on this topic are equivocal, and there are various reasons to suggest that anabolic resistance is not a characteristic of aging per se (Burd et al 2012a, b). Data from our lab Pennings et al 2011b) as well others (Paddon-Jones et al 2004;Symons et al 2007Symons et al , 2011) have failed to detect any age-related differences in the post-prandial muscle protein synthetic response to dietary protein ingestion. A classic work by Volpi et al (2000) indicates that the proposed age-related blunting of the post-prandial muscle protein synthetic response to food intake may be more pronounced under conditions where both amino acids and carbohydrates are administered.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, data on this topic are equivocal, and there are various reasons to suggest that anabolic resistance is not a characteristic of aging per se (Burd et al 2012a, b). Data from our lab Pennings et al 2011b) as well others (Paddon-Jones et al 2004;Symons et al 2007Symons et al , 2011) have failed to detect any age-related differences in the post-prandial muscle protein synthetic response to dietary protein ingestion. A classic work by Volpi et al (2000) indicates that the proposed age-related blunting of the post-prandial muscle protein synthetic response to food intake may be more pronounced under conditions where both amino acids and carbohydrates are administered.…”
Section: Discussionmentioning
confidence: 74%
“…Clearly, age does not necessarily impair the capacity to direct ingested protein towards muscle protein synthesis. Using this approach, we extend on a previous work from our lab Pennings et al 2011b) as well as from other labs (Paddon-Jones et al 2004;Symons et al 2007Symons et al , 2011Chevalier et al 2011), further supporting the concept that anabolic resistance is not a characteristic of aging per se (Burd et al 2012a). We speculate that impairments in the post-prandial muscle protein synthetic response are likely more evident in more compromised, frail, and sedentary elderly populations, especially during short periods of hospitalization, bed rest, and/or immobilization Tieland et al 2012;Burd et al 2012a), as opposed to the healthy, independently living elderly included in the present study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There is clear evidence that increased amino acid or protein availability can enhance muscle protein synthesis and anabolism in young and older subjects [19][20][21]22 • ]. It has, however, been suggested that the recommended dietary allowance for protein (0.8 g/kg/day) may not be sufficient for older adults to maintain their muscle mass.…”
Section: Nutrient Intake On Amino Acid Metabolism In Agingmentioning
confidence: 99%
“…Ez az elágazó láncú esszenciális aminosav aktiválja mind az inzulinfüggő, mind pedig az inzulintól független jelátviteli utat a fehérjeszintézis folyamatában, ezzel támogatva az izom-hipertrófia folyamatát [37]. A kezdeti laboratóriumi vizsgálatok, majd a humán kutatások arra is rámutatnak, hogy a bevitt fehér-jemennyiség napi eloszlása is szerepet játszik [38,39]. Minden főétkezésre ajánlott 20-30 grammos magas minőségű fehérjét biztosítani, vagyis a reggeli, az ebéd és a vacsora proteintartalma is közel azonos legyen.…”
Section: Megbeszélésunclassified